Programa De Gobierno De Datos Para El Área De Emisiones De Pólizas De Polizapro (2024)
The data governance program of PólizaPro is important, as the company operates in the insurance industry and handles a large amount of information. This program ensures data accuracy, quality, and compliance. In the past, PólizaPro faced issues such as poor data quality, outdated systems, and opaque practices, which affected its credibility and reputation. The main objective of this project is to design a data management solution based on DMBOK. This includes creating and improving information management in policy implementation plans, assessing the company's current situation, and developing data sheets to determine the necessary actions and policies for implementing the best information management plan. This project is necessary to improve data quality, optimize processes, and develop data management methods to support decision-making, in line with the company's strategic objectives.